DO GOVERNANCE MECHANISMS MATTER FOR CARBON PERFORMANCE? EXPLORING BOARD SIZE, SUSTAINABILITY COMMITTEES, AND GENDER DIVERSITY - Marselita, Octa; Desi Adhariani (Faculty of Economics and Business University of Mataram, 2025)
The global climate crisis has intensified pressure on corporations to reduce carbon emissions, particularly in developing countries. This study examines the relationship between corporate governance—board size, the presence of a sustainability committee, and board gender diversity—and carbon emission intensity in publicly listed companies in Indonesia and Malaysia over the period 2016–2023. Using the First-Difference GMM approach on 888 firm-year observations, the findings show that board size is negatively and significantly associated with emission intensity, while no significant relationships are found for sustainability committees and gender diversity. These results highlight the importance of strengthening the substantive function of sustainability committees, enhancing meaningful gender participation, and ensuring regulatory support so that corporate governance can make a tangible contribution to emission reduction.